A novel feedforward control strategy for simultaneous nitrification and denitrification (SND) in aerobic granular sludge sequential batch reactor (AGS-SBR). (15th April 2020) - Chen, Wenjing; Lu, Yiming; Jin, Quan; Zhang, Miao; Wu, Jun
Abstract: The nitrogen removal in the aerobic granular sludge sequential batch reactor (AGS-SBR) can be achieved by the simultaneous nitrification and denitrification (SND) mode, or by the separated nitrification and denitrification stages. The SND offers a simpler operation structure than the separated nitrification and denitrification. Based on the mathematical simulation, a novel control strategy was put forward to adjust the DO (dissolved oxygen) concentration to achieve the SND under dynamic fluctuated influent conditions in AGS-SBR. The control strategy aimed to achieve a small accumulation of NH4 + at the end of the aeration cycle (NH4 + setpoint value), as previous research has indicated that keeping the small NH4 + setpoint value would guarantee the optimal condition for total nitrogen (TN) removal. The SBR aeration cycle was divided into several equal control intervals. The DO was adjusted in every control interval to reach the NH4 + set point. The results revealed that the control strategy was able to maintain the NH4 + setpoint value and achieve satisfactory TN removal. The control interval should be less than 30 min to prevent deviation of NH4 + concentration from its setpoint value. A minimum aeration duration of 3 h was required to achieve satisfactory SND. Highlights: Simultaneous nitrification-denitrification in aerobic granular sludge was promoted. A novel feedforward control strategy was put forward. A small accumulation of NH4 + is vital for nitrogen removal. Satisfactory nitrogen removal was achieved.